Regulation of epithelial tissue homeostasis by active transepithelial transport - Huiqiong Wu; Charlie Duclut; Gregory Arkowitz; Ranjith Chilupuri; Tien Dang; Jacques Prost; Benoit Ladoux; René-Marc Mège (Proceedings of the National Academy of Sciences, 2025)
Epithelia are intricate tissues whose function is intimately linked to mechanics. While mechanobiology has primarily focused on factors such as cell-generated contractility and mechanical properties of extracellular matrix, a interesting mechanobiological paradigm highlights the role of osmotic and mechanical pressures in shaping epithelial tissues. In our study, we developed an in vitro model of cell-coated microsized hydrogel spheres (MHSs) which allows to decipher the interplay between cellular activities and tissue mechanics. Drastic, isotropic MHS compressions were observed once the epithelia reached confluence. Further studies revealed that the compression was a process independent of cell contractility but rather regulated by active transepithelial fluid flow. Compressive stresses of about 7 kPa are generated by such an active hydraulic mechanism. Tissue homeostasis is then maintained by a fine balance between cell proliferation and extrusion. Our findings demonstrate the critical role of fluid transport in generating mechanical forces within epithelial tissues. Supported by a theoretical mechanohydraulic model, a mechanistic framework for understanding the intricate interplay between cellular processes and tissue mechanics was established. These results challenge traditional views of epithelial tissue mechanics, emphasizing the pivotal influence of osmotic and mechanical pressures in shaping tissues. We anticipate that this study will advance the understanding of epithelial tissue development, the maintenance of homeostasis, and the mechanisms underlying pathological conditions.